Klasifikasi Resiko Kehamilan Menggunakan Ensemble Learning berbasis Classification Tree - Muhamad Arief Hidayat (Faculty of Computer Science, University of Jember, 2021)
In health science there is a technique to determine the level of risk of pregnancy, namely the Poedji Rochyati score technique. In this evaluation technique, the level of pregnancy risk is calculated from the values ​​of 22 parameters obtained from pregnant women. Under certain conditions, some parameter values ​​are unknown. This causes the level of risk of pregnancy can not be calculated. For that we need a way to predict pregnancy risk status in cases of incomplete attribute values. There are several studies that try to overcome this problem. The research